DEVELOPMENT OF MODULAR FACILITIES FOR PICKUP TRUCKS AS ACCORDING TO BANDUNG MODIFICATION CUSTOMS - Dhanurendra Zijlstra, Prasidya
Since the last decade, the pickup truck has become a popular choice for new adopters and old users as a mobile commercial platform by way of converting the vehicle into task-specific forms. It is not uncommon to find these vehicles avoiding safety guidelines or carrying way over their weight capacity, it should also be considered that most of pickup trucks on the road currently are not maintained to optimal physical conditions due to the high cost of vehicle maintenance. Besides that, there is also a cultural aspect to consider that may impact a product’s development, pickup drivers of all kinds both in career work and independent labor have formed communities differentiated by their region of operation, what brand of pickup truck they use, and what kind of goods they transport. This cultural aspect serves a functional purpose yet does not exclude decorative modifications as well, similar behavior can also be observed in other motor-culture communities, pickup truck drivers would modify the appearance, shape, sound, and other aspects to express their personalities or to associate themselves within one working group, company, or community. There are several methods applied in this research paper including literary research based on the theoretical basis that relates to transport vehicles and the modifications done by the users. Observational and interview data were the two most influential research sources for this paper, both of which were conducted within the scope of Kota Bandung and conducted in-situ. The results of this research contributed to the design process of the final project in the form of attachments to the body of the pickup truck, this attachment is the basic module of a modular system that can be installed and disassembled through a turn and lock system. This product hopes to fulfill the potential of pickup trucks as multipurpose vehicles as well as to meet the needs of the Indonesian people who require vehicles that are used for long periods of time while minimizing maintenance requirements.